2021
DOI: 10.1038/s41598-021-87524-0
|View full text |Cite
|
Sign up to set email alerts
|

The whole is greater than its parts: ensembling improves protein contact prediction

Abstract: The prediction of amino acid contacts from protein sequence is an important problem, as protein contacts are a vital step towards the prediction of folded protein structures. We propose that a powerful concept from deep learning, called ensembling, can increase the accuracy of protein contact predictions by combining the outputs of different neural network models. We show that ensembling the predictions made by different groups at the recent Critical Assessment of Protein Structure Prediction (CASP13) outperfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 21 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…The diverse models in our study were due to different random splits of the data, randomization of the SMOTE process, and randomization of the initial sets of weights and biases of the ANN models prior to training. Previous studies have used ensemble processes to improve predictions over those made by individually trained models [ 37 , 38 ]. An additional advantage of the ensemble process in our study was that the variability of the predictions for individual patient records could be determined.…”
Section: Discussionmentioning
confidence: 99%
“…The diverse models in our study were due to different random splits of the data, randomization of the SMOTE process, and randomization of the initial sets of weights and biases of the ANN models prior to training. Previous studies have used ensemble processes to improve predictions over those made by individually trained models [ 37 , 38 ]. An additional advantage of the ensemble process in our study was that the variability of the predictions for individual patient records could be determined.…”
Section: Discussionmentioning
confidence: 99%
“…In late 2018, our team began the onboarding phase by attending the CASP13 conference and collecting relevant literature. After about six months, we understood the best methods in the field and designed new approaches based on them (Billings et al, 2019(Billings et al, , 2021Stern et al, 2021). Before the official CASP14 challenge began, the assessment center launched a communitywide experiment to help with the structure determination of COVID-19-related proteins (Kryshtafovych et al, 2021).…”
Section: Preparing For Executing and Evaluating The Casp14 Challengementioning
confidence: 99%
“…When only sequences are given as inputs, PCP is even harder because the unbound structures of individual chains and auxiliary information on the complex interfaces are unavailable. Deep learning has enabled substantial progress in quite a few computational structural biology tasks, such as protein contact 8–10 , tertiary structure prediction 1113 , and cryo-electron microscopy structure determination 14,15 . Recently, AlphaFold-Multimer 16 has been shown that it outperforms prior protein complex prediction systems, such as the fast Fourier transform-based method ClusPro 1719 .…”
Section: Introductionmentioning
confidence: 99%
“…Deep learning has enabled substantial progress in quite a few computational structural biology tasks, such as protein contact [8][9][10] , tertiary structure prediction [11][12][13] , and cryo-electron microscopy structure determination 14,15 . Recently, AlphaFold-Multimer 16 has been shown that it outperforms prior protein complex prediction systems, such as the fast Fourier transform-based method ClusPro [17][18][19] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation